Enhanced Fibrogenesis Activity in Diabetic Wound Using 20% Anredera scandens (L.) Moq. Leaves Extract Ointment in Sprague dawley Rats: Peningkatan Aktivitas Fibrogenesis pada Penyembuhan Luka Diabetik Menggunakan Salep Ekstrak Daun Anredera scandens (L.) Moq. 20% pada Tikus Sprague Dawley - Ardinata, I Putu Riska; Setiawan, Putu Yudhistira Budi; Hita, Putu Gede Adi Purwa (Universitas Tadulako, 2024)
Background: In diabetic conditions, decreased glucose-6-phosphate dehydrogenase activity results in reduced nitric oxide synthesis. Reduced nitric oxide synthesis results in the production of ROS. This may impede the processes of angiogenesis and vasoconstriction and prolong inflammation. Objective: We were interested in investigating the mechanism by which 20% of Anredera scandens leaves extract ointment increases fibrogenesis activity because this condition can affect the development of damaged skin tissue. This study's design is a post-test-only laboratory experiment. Material and methods: The study employed male Sprague dawley strain rats that were induced with 40 mg/kgBW of STZ. The mice were divided into four groups: the negative group (which got diabetic wounds only), the positive group (which got Gentamicin ointment), and the test group (which got 20% extract ointment). Results: The skin tissue from each group was then examined histopathologically. After receiving 20% ointment of Anredera scandens leaves extract, the test group's mean fibrogenesis histopathology score on day 14 was significantly higher (P=0.022) at 3.75 than that of the negative group, which had a mean score of 2.75. Following that, the skin tissue of both the extract test group and the normal group was examined histopathologically. In comparison to the normal group mean score of 4.0 on day 14, the test group, which received 20% ointment of Anredera scandens leaves extract, had a non-significant (P=0.317) mean fibrogenesis histopathology score of 3.75. Subsequently, skin tissue was examined histopathologically for both the positive and normal groups. According to the results, on day 14, the positive group's average fibrogenesis histopathology score was 3.5, while the normal group's average score was 4.0. This difference was not statistically significant (P=0.127). Conclusions: Thus, it can be said that 20% Anredera scandens leaf extract ointment is comparable to gentamicin ointment in its capacity to promote fibrogenesis activity in diabetic wounds.